Automatic Cloth Hanger System Using IoT - Adzmi, Noraiman; bakar, Lilywati; Abdul Wahab, Zurina (Progress in Engineering Application and Technology, 2022)
Hanging clothes is a very difficult task to do for working citizens in Malaysia where the probability of rain is high. The objectives of this proposed project are to help in keeping the clothes away from the rain and send information about the situation of the proposed project to the user through the IoT platform. The project used DHT and rain sensors to gather input, a linear actuation using DC stepper motor for mechanical movement, and the Blynk interface as an IoT platform that collects information from the project. The Blynk interface will help in displaying the output perform by the project such as displaying temperature, humidity, rain, and the condition of the hanger (extend/retract).